Spatial-temporal heterogeneity of vegetation reduces concentration of atmospheric pollution particles in the East China Metropolitan Area - Tong Liu; Jiaqi Yao; Yongqiang Cao; Tianling Qin; Qingyang Wu; Fan Mo; Haoran Zhai; Haiying Gong; Zihua Liu (Ecological Indicators)
Air pollution, particularly PM2.5 and PM10, presents substantial challenges in China’s major urban agglomerations: Beijing-Tianjin-Hebei (BTH), Yangtze River Delta (YRD), and Pearl River Delta (PRD). Vegetation reduces fine particles in the air via dry deposition, offering a natural, green, and cost-effective means of alleviating air pollution. This study used multi-source satellite remote sensing data as a substitute for traditional ground station data and applied an improved UFORE model to analyze the spatiotemporal distribution of vegetation dry deposition from 2001 to 2020 in these regions. The results of this study revealed the following: 1) PRD showed the highest per-unit area deposition, particularly for PM10. Peak deposition occurred in 2013, followed by a decline in pollutant concentrations, whereas air quality improvement increased. 2) Dry deposition showed a strong positive correlation with the leaf area index, with a maximum correlation of 0.91. Excessive pollutant concentrations suppressed dry deposition. 3) Forest land generally has a strong dry deposition capacity; however, in some areas, farmlands exhibited relatively high unit area deposition, with farmland dry deposition accounting for 30–50% of the total dry deposition in those regions. These findings are valuable for air pollution control, green space planning, and sustainable development in urban regions.